2014
DOI: 10.1128/jcm.03553-13
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Xpert MTB/RIF for Extrapulmonary Tuberculosis Specimens: Establishing a Laboratory Testing Algorithm for South Africa

Abstract: e South Africa implemented Xpert MTB/RIF as the initial diagnostic test for pulmonary tuberculosis (TB). Xpert MTB/RIF's accuracy for diagnosing extrapulmonary tuberculosis (EPTB) was investigated. EPTB specimens (n ‫؍‬ 7,916) from hospitalized patients received over a 6-month period at a high-throughput TB referral laboratory in Johannesburg were investigated. Largevolume specimens were centrifuged, tissue biopsy specimens homogenized, and all specimens checked for growth of contaminating bacteria on blood ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
59
4
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 22 publications
10
59
4
4
Order By: Relevance
“…Suboptimal performance of the assay was observed for various body fluids, with sensitivity ranging from 18% to 40%, which is consistent with several previous studies [7][8][9][10][11][12]. The present study also indicates exemplary performance of the assay in patients with cold abscesses and lymph nodes and these findings are similar to previously published literature [7][8][9]13].…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Suboptimal performance of the assay was observed for various body fluids, with sensitivity ranging from 18% to 40%, which is consistent with several previous studies [7][8][9][10][11][12]. The present study also indicates exemplary performance of the assay in patients with cold abscesses and lymph nodes and these findings are similar to previously published literature [7][8][9]13].…”
supporting
confidence: 82%
“…The present study also indicates exemplary performance of the assay in patients with cold abscesses and lymph nodes and these findings are similar to previously published literature [7][8][9]13]. The difference in sensitivity could be attributed to the fact that in lymph nodes and its aspirates the bacteria are localised to the site of infection, whereas in body fluids, presence of PCR inhibitors and the paucibacillary nature of the specimens may result in lower sensitivity.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Twenty-one studies (2,167 patients) and 10 studies (937 patients) used a microbiological standard (mycobacterial culture) (7, 8, 13-16, 19, 20, 22-34) or a composite reference standard (CRS) (7, 14-18, 21, 22, 24, 28), respectively, to assess the diagnostic accuracy of GeneXpert (see Table S3). Seven studies performed Xpert MTB/RIF on frozen pleural fluid (7,15,19,21,23,28,30), while the remaining used fresh samples (see Table S4). Nine studies concentrated the pleural fluid sample by centrifugation before performance of GeneXpert (7, 8, 16-18, 20, 22, 24, 29).…”
mentioning
confidence: 99%
“…et al 12 in 2014, by Xpert MTB/RIF, which provided an early diagnosis of RIF resistance (9.6%) in 25/260 cases (with 100% specificity). In this study, only 3 samples were found to be rifampicin resistant out of 123 samples.…”
mentioning
confidence: 99%